"Friendly" Initiatives: An Emerging Approach to Improve Communities for Vulnerable Populations. Issue 1 (2nd January 2017) - Lehning, Amanda J.; Smith, Richard J.; Kim, Kyeongmo
ABSTRACT: A growing number of cities and towns are implementing "friendly" initiatives to change the community's social and physical infrastructure to address the needs of a particular vulnerable segment of their population. Three prominent examples are aging-friendly, child-friendly, and immigrant-friendly initiatives. Although the limited but growing literature describes these initiatives as promising strategies to improve the quality of life of the targeted population, to date there has been little written about the underlying goals, values, and assumptions of these efforts. Using the value-critical approach, this article aims to better understand these aspects of population-friendly initiatives by examining the scholarly and grey literature. Social workers engaged in community and policy practice can play a key role in these efforts and call attention to the ways they may alleviate or exacerbate inequities. Future research is needed to assess the effects of these initiatives on their targeted population as well as other community residents.